Development of a community-based post-coronavirus care and management system for individuals living with COVID-19 - Hathaichanok Buajaroen; Darin Portangtam; Paisan Simalaotoa; Ubonrat Sirisukpoca; Tapanee Sousengaee; wariya Chamkhan (Nursing and Midwifery Studies)
Background: Post-COVID-19 care addresses the ongoing health challenges faced by individuals who have recovered from the virus. Many patients experience persistent symptoms, commonly referred to as long COVID, which can impact both physical and mental health. Consistent follow-up care is essential for these patients, emphasizing the need for a comprehensive approach. The development of systems that provide continuous care, particularly through health technology, is crucial for supporting recovery and assisting patients in adapting to life after COVID-19. Objectives: This study aimed to develop community-based care and management guidelines for post-COVID-19 patients, provide ongoing care for individuals living with COVID-19, and assess the effectiveness of these guidelines. Methods: This action research study included 50 professional nurses from Nakhon Pathom Province, Thailand, in 2024. Participants were selected through purposive sampling, with all having at least one year of experience in caring for COVID-19 patients. Data were collected via semi-structured group interviews and five focus groups, each consisting of 10 participants, along with 10 individual interviews to explore unresolved aspects. The guiding interview questions were validated by three experts in nursing and infectious diseases. Data analysis utilized content analysis, triangulation, and synthesis of key points to ensure credibility and applicability. Results: The findings identified critical components of the post-COVID-19 care guidelines: 1) Initial health assessments and screening for pre-existing conditions; 2) Monitoring residual symptoms for up to one-year post-recovery, including respiratory issues, dermatological conditions, chronic illnesses, and exacerbations of existing conditions. New diseases and lingering psychological symptoms were also noted; 3) Health management guidelines included self-care practices utilizing digital COVID-19 information, telehealth nursing for continuous care, physical health services post-recovery, mental health services addressing psychological impacts, and referral systems for emergency care. Conclusion: Continuous care, efficient health information transfer, and technology-supported psychological and social interventions were critical for supporting post-COVID-19 patients in resuming normal life and enhancing their quality of life.